2015
DOI: 10.1007/s10198-015-0700-2
|View full text |Cite
|
Sign up to set email alerts
|

Price offers of pharmaceutical procurement in China: evidence from Guangdong province

Abstract: Using a sample from the pharmaceutical procurement in Guangdong, China, over the period from 2007-2009 and a data set of comprehensive potential bidders, this article analyzes the determinants of bidding behaviors in the presence of sample selection. Bidding patterns between highly competitive and less competitive groups are also examined. Price differentials are further decomposed to explain factors that account for the gap. We find that a high level of competitiveness and more winning experiences induce manu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…Included studies were published from January 1 st 2012 to December 31 st 2021 and were written in English. The geographical distribution of the studies included 3 studies from the Slovak Republic [25][26][27] , 1 in Brazil [28] , 1 in Czech [27] , 4 in China [13,[29][30][31] , 1 in South Africa [32] , 1 in Cyprus [33] , 1 in Chile [34] , 1 in European countries [35] and 1 in India [36] .…”
Section: Study Characteristics and Findingsmentioning
confidence: 99%
See 3 more Smart Citations
“…Included studies were published from January 1 st 2012 to December 31 st 2021 and were written in English. The geographical distribution of the studies included 3 studies from the Slovak Republic [25][26][27] , 1 in Brazil [28] , 1 in Czech [27] , 4 in China [13,[29][30][31] , 1 in South Africa [32] , 1 in Cyprus [33] , 1 in Chile [34] , 1 in European countries [35] and 1 in India [36] .…”
Section: Study Characteristics and Findingsmentioning
confidence: 99%
“…Most of the articles (n=12) were quasi-experimental studies [13,[25][26][27][28][29][30][31][32][33][34][35][36] and one was a two cross-sectional study [30] . Nine of the 13 studies showed the evaluation of only the e-bidding system without a comparison system [13,[26][27][28][29][30][31][32][33][34][35] .…”
Section: Study Characteristics and Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…In individual studies, systems allowing for mark-ups (eg, processing costs or profit passed on to purchaser), degree of market competitiveness, the generics market proportion and degree of governmental intervention (reference pricing and education about efficacy of generics) have been found to influence drug prices in some countries. [14][15][16][17][18][19] A systematic analysis of modifiable drug price determinants that are published in drug price comparison studies is, however, missing. Therefore, in this systematic review, we aim to identify determinants of drug prices and more specifically modifiable determinants that may serve as potential targets for drug price optimisation.…”
Section: Introductionmentioning
confidence: 99%